PERENCANAAN PENGEMBANGAN TERMINAL BANDARA UDARA DJALALUDDIN GORONTALO - Ismet Ahmad Asui (Universitas Bina Taruna Gorontalo, 2022)
The airport in Gorontalo is known as Djalaludin Airport which was taken from an Indonesian Air Force pilot who was the best son of Indonesia from the Gorontalo area, namely Lt. Col. Pnb Djalaluddin Tantu who was declared dead during the Dwikora operation in Malaysia. Before becoming Djalaludin Airport in 1974, initially this airport was named Tolotio Airport since it was founded in 1955 because of its location in Tolotio village, Tibawa district, Gorontalo regency. The purpose of this study is to find out whether the Djalaluddin airport terminal is feasible for the development of the terminal area of ​​​​the number of passengers. Data from the site survey and the results of the analysis of space requirements calculations with sources: (Airport Passenger Terminal, SKEP 347/XII/1999 (ICAO Annex 9 Reference on Facilities). The results show that Djalaluddin Airport is still feasible to accommodate passengers at this time. With Comparison of the actual area of ​​6122 m2 and the theoretical 5270 m2. And the results of the regression analysis show that in 2032 it was obtained 722,440 passengers. The actual area of ​​the Djalaludin airport terminal is 6032 m2, so it needs to be redeveloped so that it can accommodate the number of passengers in the coming year.